Assessment of Dental Anxiety in Adults Undergoing Dental Procedures in Dow International Dental College - Wajiha Anzar; Ashar Afaq; Qaiser Ali Baig (Journal of the Dow University of Health Sciences, 2017)
Objectives: The objective of this study was to assess anxiety level in patients seeking dental treatment in Dow International Dental College and its relationship with social factors, demographic factors and according to dental procedures using Modified Dental Anxiety Scale by Corah.